Anatomical aberration of palmaris longus agenesis muscle through clinical examination in relation to gender and hand dominance - Quratulain Javaid; Ambreen Usmani; Ambreen Surti (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of agenesis of palmaris longus muscle and its association with gender and hand dominance. Method: The cross-sectional descriptive study was conducted at the Bahria University Medical and Dental College, Karachi, from March 2021 to November 2021, and comprised medical students of either gender from 1st, 2nd and 3rd year of studies. Clinical examination of palmaris longus was done by using the classic Schaeffer’s test, and it was confirmed using the Thompson’s test. The agenesis of palmaris longus muscle and its association with gender and hand dominance was also tested. Data was analysed using SPSS 23. Results: Of the 200 participants, 114(57%) were female and 86(43%) were male. The overall age range was 18-23 years. Of the total, 195(97.5%) subjects were right hand dominant and 5(2.5%) were left hand dominant. Agenesis was found in 67(33.5%) subjects with no significant difference in terms of gender or hand dominance (p>0.05). Statistically significant difference (p=0.01) was found related to bilateral agenesis. Conclusion: Bilateral agenesis was found significantly more in females compared to the males, while palmaris longus agenesis and hand dominance had no significant association. Key Words: Anatomical, Aberration, Palmaris longus, Agenesis, Clinical examination, Gender, Hand dominance.